DNA barcoding of alien invertebrates and biological control agents in South Africa: a review - Pitcher, Tristan; Ndaba, Abusisiwe; Jacobs, Adriaana; Hamer, Michelle; Janion-Scheepers, Charlene (African Entomology, 2024)
The rate of human-induced spread of organisms is increasing with globalisation. In addition, climate change is altering ecosystems, enabling species to invade new environments. Invertebrates are particularly well-suited to invasion due to their generally small size and short generation time and their impacts can be extreme. Therefore, reliable species identification is a fundamental requirement for intercepting such alien organisms at borders and managing their populations, but traditional taxonomic identifications can be time-consuming and often require expertise. DNA barcoding is a molecular technique that is rapid, cost-effective and does not require taxonomic expertise. In this study, we compiled an updated checklist of all known alien invertebrate species in South Africa and their status on the Barcode of Life Data System (BOLD) using previous published records and literature. In total, 1013 alien invertebrate species, including 132 biocontrol agents, were found. Insects, predominantly hemipterans, comprised most of the alien species. Overall, 66.8% of alien species in the dataset were accessioned on BOLD. However, few of these alien invertebrate records were South African specimens (24.3%). This study marks the first comprehensive DNA barcoding checklist of alien and biocontrol agent invertebrates in South Africa. The findings are promising because many alien species can be identified to a Molecular Operational Taxonomic Unit (MOTU) or Barcode Index Number (BIN) on BOLD using their COI barcode. However, there is a gap in available barcodes for alien invertebrates. As climate change alters the biogeography of alien species, baseline molecular data such as COI barcodes will be invaluable in monitoring and limiting their spread.